(untitled) (Mugda Medical College Journal, 2025)
Morphometry of the proximal end of the femur is important to orthopaedic surgeons for the selection of appropriate size of internal fixators and implants. Similarly, prosthetists need it for designing population specific hip joint prosthesis. Besides, morphometry of the proximal end of the femur shows gender variation, which helps the forensic experts in determination of sex. Moreover, anatomists and anthropologists may use it for the purpose of comparative studies. Therefore, the present study was designed to provide a standard data of different morphometric parameters of the proximal end of the femur in an adult Bangladeshi population through radiographic analysis, and observe differences between male and female, if any. This cross-sectional, analytical study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, Bangladesh, between July 2020 and June 2021. Standardised anteroposterior pelvic radiographs of 70 apparently healthy adult Bangladeshi patients (35 male and 35 female) were taken. All were reported as normal by a specialist radiologist. Data was collected in a data sheet. The diameter of the femoral head, width and length of the femoral neck and femoral neck-shaft angle were measured unilaterally using MB ruler software after zooming in and increasing resolution of the radiographs. The mean diameter of the femoral head, length and width of the femoral neck, and femoral neck-shaft angle in our total study population were found 47.67±4.47 mm, 51.44±5.36 mm, 31.90±3.71 mm, and 131.57±3.7° respectively. Sexual dimorphism was observed in the diameter of the femoral head (51.22±2.57 mm vs. 44.13±2.84 mm), length of the femoral neck (53.86±0.97 mm vs. 49.03±4.33 mm), and width of the femoral neck (34.46±2.79 mm vs. 29.59±3.05 mm (p<0.001). However, no difference was found in femoral neck-shaft angle between male and female (132.11±4.04° vs. 131.16±3.69°) (p>0.05). Mugda Med Coll J. 2025; 8(2): 90-95